2017
DOI: 10.1002/2016gl071932
|View full text |Cite
|
Sign up to set email alerts
|

Water vaporization promotes coseismic fluid pressurization and buffers temperature rise

Abstract: We investigated the frictional properties of carbonate‐rich gouge layers at a slip rate of 1.3 m/s, under dry and water‐saturated conditions, while monitoring temperature at different locations on one of the gouge‐host rock interfaces. All experiments showed a peak frictional strength of 0.4–0.7, followed by strong slip weakening to steady state values of 0.1–0.3. Experiments which used a pore fluid with a constant drainage path to the atmosphere showed the development of a temperature plateau beyond 100°C, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 43 publications
(65 reference statements)
10
85
0
Order By: Relevance
“… The occurrence of fluidized fault rock textures preserved along the TMF (Figures d and e), probably testifying for episodic and impulsive fault rock fluidization during seismic slip, is consistent with the evidence of fluid overpressures at hypocentral depths in the Italian Central Apennines based on focal mechanism tomography [ Terakawa et al , ]. In fact, seismic slip under these fluid‐rich conditions would result in the possible activation of seismic‐related fluid thermal pressurization [e.g., Rice , ; Chen et al , ]. Slow and continuous deformation along foliation surfaces (Figure g) and mantled clasts (Figure i) can promote tectonic elastic strain energy dissipation during interseismic phases through permanent aseismic creep [e.g., Collettini et al , ]. In addition, CR‐AFM measurements show that phyllosilicates behave more viscously (i.e., higher loss tangent and lower loss modulus values; Figures and ) than calcite clasts.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“… The occurrence of fluidized fault rock textures preserved along the TMF (Figures d and e), probably testifying for episodic and impulsive fault rock fluidization during seismic slip, is consistent with the evidence of fluid overpressures at hypocentral depths in the Italian Central Apennines based on focal mechanism tomography [ Terakawa et al , ]. In fact, seismic slip under these fluid‐rich conditions would result in the possible activation of seismic‐related fluid thermal pressurization [e.g., Rice , ; Chen et al , ]. Slow and continuous deformation along foliation surfaces (Figure g) and mantled clasts (Figure i) can promote tectonic elastic strain energy dissipation during interseismic phases through permanent aseismic creep [e.g., Collettini et al , ]. In addition, CR‐AFM measurements show that phyllosilicates behave more viscously (i.e., higher loss tangent and lower loss modulus values; Figures and ) than calcite clasts.…”
Section: Discussionsupporting
confidence: 81%
“…At 0.001 m s −1 , both in dry and in wet conditions, the effective friction coefficient (i.e., note that, in the wet experiments, the pore fluid pressure cannot be measured, hence the term “effective” [e.g., Chen et al , ]) achieves a peak of ~0.6 at slip initiation and then increases almost monotonically toward a constant value of 0.7–0.8 that is eventually achieved after ~0.5 m of slip (Figure c). At seismic slip rates (1 m s −1 ), gouges in the three configurations (both in dry and in wet conditions) show a strong dynamic weakening (i.e., friction drop) after a strengthening phase, which is defined here as the distance to the onset of dynamic weakening, D ow (Figures d and e) [ Smith et al , ].…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Our study shows that at local thermal equilibrium, the occurrence of vaporization could buffer the macrotemperatures of the fault gouge to not exceed the boiling temperatures (Figures ). This is consistent with our recent HVF experiments [ Chen et al ., ], in which we observed that with the presence of liquid water, the macrotemperatures of the gouge layer subjected to frictional heating did not surpass the boiling temperatures—except when the water had completely escaped the slipping zone. This temperature buffering effect may explain why low‐temperature anomalies were measured in the principal slip zones of large earthquakes at 0.3–0.6 km borehole depths in drilling campaigns (e.g., the 1999 Chi‐Chi earthquake on the Chelungpu fault [ Tanaka et al ., ] and the 2008 Wenchuan earthquake on the Longmenshan fault [ Li et al ., ]).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, water vaporization was commonly observed in previous rotary shear tests in samples deformed at V eq ≥ 0.61 m/s (Wang et al, ). Coseismic experimental studies of fault gouges have also reported water vaporization, which is expected to be an important mechanism for fault frictional weakening, especially in shallow faults (Brantut et al, ; Boutareaud et al, ; Chen, Niemeijer, Yao, & Ma, , Chen, Niemeijer, & Fokker, ; Kitajima et al, , ; Wada et al, ).…”
Section: Introductionmentioning
confidence: 99%